SysML for the Analysis of Product-Service Systems Requirements - Durugbo, Christopher; Hutabarat, Windo; Tiwari, Ashutosh; Alcock, Jeffrey R. (Cranfield University, 2010)
In this paper, the Systems Modelling Language (SysML) is introduced as a technique for the design of aproduct-service system (PSS). In examples of the requirements diagram in SysML, this paper shows that:(1) a PSS can be analysed by the SysML technique, and (2) the SysML can model the requirements of aPSS in orientations according to product, use or result. Recommendations based on the example will thenbe used to suggest improvements in the design of a PSS.